Kesupant sebagai Etika Manusia Dayak Keninjal Desa Laman Bukit Kalimantan Barat Menurut Perspektif Etika Aristoteles - Purba Kencana, Julio; Pasi, Gregorius (Borneo Review, 2023)
This study discusses decency as an ethic of the Dayak Keninjal human in the village of Laman Bukit. Each tribe in its relationship with others in society must have a rule as social ethics. The social ethics then become a rule or law in common life. The Dayak Keninjal tribe of Laman Bukit village also has a concept of social ethics and rules of living together which is called Kesupant. They or the Dayak Keninjal people in the village of Laman Hill view decency as a liberating law in the ethics of daily interaction. Meanwhile, according to Aristotle, ethics is a moral obligation in living together in order to achieve the bonum commune or the common good. The method used in this study is the method of literature study and interviews with the traditional leader of the Dayak Keninjal tribe. Meanwhile, the methodology used in this study is a reflection of philosophy in Aristotelian ethics as the main scalpel that the author uses. This study found that the Dayak Keninjal people long before they knew civilization already had the concept of daily social ethics known as kesupan. By knowing concepts like these, we can look for local cultural riches that have other philosophical values.